2014
DOI: 10.1186/s40557-014-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long Working Hours on Self-reported Hypertension among Middle-aged and Older Wage Workers

Abstract: ObjectivesMany studies have reported an association between overwork and hypertension. However, research on the health effects of long working hours has yielded inconclusive results. The objective of this study was to identify an association between overtime work and hypertension in wage workers 45 years and over of age using prospective data.MethodsWage workers in Korea aged 45 years and over were selected for inclusion in this study from among 10,254 subjects from the Korean Longitudinal Study of Ageing. Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
1
31
0
4
Order By: Relevance
“…Perceived stress then contributes to elevated blood pressure. Similarly, a recent study on the effect of working hours and hypertension in Koreans showed that there was a higher hazard ratio of hypertension in female workers than male workers [ 43 ]. The authors explained that women have to bear the burden of a job and domestic work, and moreover, the working burden is higher for female workers than male workers.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress then contributes to elevated blood pressure. Similarly, a recent study on the effect of working hours and hypertension in Koreans showed that there was a higher hazard ratio of hypertension in female workers than male workers [ 43 ]. The authors explained that women have to bear the burden of a job and domestic work, and moreover, the working burden is higher for female workers than male workers.…”
Section: Discussionmentioning
confidence: 99%
“…A response of, "I do not have enough money", was defined as "economic burden"; a response of, "Most hospitals were closed when I had free time to visit a hospital", was defined as "lack of time"; and other responses were defined as "other", such as, "I have difficulty making a hospital appointment", "Using transportation is hard", "I hate waiting for such a long time in hospital", "Symptoms were mild", and "other" for other causes. (32).…”
Section: Unmet Healthcare Needmentioning
confidence: 99%
“…Changes in the activity of the autonomic, sympathetic, and/or parasympathetic nervous systems have been suggested as potential mechanisms through which working long hours influences cardiovascular health, as has increased blood pressure. 11 Substantial evidence exists that working long hours is associated with many CVD-related risk factors (e.g., hypertension, 12, 13 heart rate variability, 14 smoking, 15 physical inactivity, 15 stress 15, 16 and depression 17 ), and it has been suggested that increasing work hour durations may have a dose-response relationship with CVD. 9, 18 …”
Section: Introductionmentioning
confidence: 99%